Nursing Doctorates in Brazil: research formation and theses production - Carmen Gracinda Silvan Scochi; Francine Lima Gelbcke; Márcia de Assunção Ferreira; Maria Alice Dias da Silva Lima; Katia Grillo Padilha; Nátali Artal Padovani; Denize Bouttelet Munari (Universidade de São Paulo, 2015)
OBJECTIVE: to analyze the formation of nursing doctorates in Brazil, from theses production, disciplines and other strategies focusing on research offered by courses.METHOD: a descriptive and analytical study of the performance of 18 doctoral courses in nursing, running from 1982 to 2010, and defended their theses between 2010-2012.RESULTS: 502 theses were defended in this period, most linked to the online research process of health and nursing care. There are gaps in the knowledge of theoretical and philosophical foundations of care, nursing history and ethics. There are also weaknesses in the methodological design of the theses, with a predominance of descriptive and/or exploratory studies. This was consistent with international standards set with regards to the proposition of research of disciplines and complementary strategies in forming the doctorate.CONCLUSION: despite the efforts and advances in research formation, it is essential to expand to more robust research designs with a greater impact on production knowledge that is incorporated into practice.